"Doing Geography": Evaluating an Independent Geographic Inquiry Assessment Task in an Initial Teacher Education Program. Issue 6 (1st November 2016) - Harte, Wendy; Reitano, Paul
Abstract: The assessment task of the final course in a bachelor of secondary education program is examined for opportunities for preservice geography teachers to achieve the course aims of integrating, consolidating, applying, and reflecting on the knowledge and skills they have learned during their initial teacher education program. The results show that the preservice teachers did better in some areas (integrating, consolidating, and reflecting) than in others (applying). This has implications for curriculum renewal in geography methods courses—specifically to provide more opportunities for preservice teachers to practice applying the knowledge and skills they have gained during the program, essential for their future roles as senior geography teachers.